2011
DOI: 10.1007/s00330-011-2227-y
|View full text |Cite
|
Sign up to set email alerts
|

Raw data-based iterative reconstruction in body CTA: evaluation of radiation dose saving potential

Abstract: Intra-individual comparisons of image quality of body CTA suggest that raw data-based iterative reconstruction allows for dose reduction >50% while maintaining image quality. Key Points • Raw data-based iterative reconstruction reduces image noise and improves image quality as compared to filtered back projection • At a similar radiation dose, raw data-based iterative reconstruction improves the sharpness of vessel contours • In body CTA a dose reduction of >50% might be possible when using raw data-based iter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
125
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(131 citation statements)
references
References 12 publications
(11 reference statements)
5
125
0
1
Order By: Relevance
“…Most important, the spatial resolution was preserved, which was substantially better than that in other scanners without the comb filter techniques. 6 Iterative reconstruction has the potential to reduce image noise and radiation dose compared with standard filtered back-projection reconstruction algorithms in many studies, [14][15][16][17] including in the temporal bone. 13 The amount of dose reduction highly depends on the specific vendor, scanner platform and imaging task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most important, the spatial resolution was preserved, which was substantially better than that in other scanners without the comb filter techniques. 6 Iterative reconstruction has the potential to reduce image noise and radiation dose compared with standard filtered back-projection reconstruction algorithms in many studies, [14][15][16][17] including in the temporal bone. 13 The amount of dose reduction highly depends on the specific vendor, scanner platform and imaging task.…”
Section: Discussionmentioning
confidence: 99%
“…Iterative reconstruction (IR) is a promising reconstruction technique that is superior to standard filtered back-projection reconstructions and theoretically can be used to improve resolution at standard radiation doses or to maintain current resolution by using a reduced radiation dose. [14][15][16][17] Recently, a new technique combining a deconvolution technique and an IR algorithm, referred to as ultra-high-resolution (UHR)-IR, has been introduced to improve dose efficiency of the zUHR mode. Phantom studies demonstrated that this technique improved dose efficiency by removing the comb filter along the cone (z) direction.…”
mentioning
confidence: 99%
“…6,7,15 This study demonstrates that half-dose CT images reconstructed using SAFIRE were superior to standard-dose images in regards to subjective im- This study found that the sharpness of the and another group selected S2 and S3, as the optimal strength levels for low-dose lung CT. 16,17,19 These differences may be influenced by body mass index (BMI), given that image noise is higher in patients with higher BMIs. 25 The mean BMI in previous studies is slightly higher than in our study.…”
Section: Discussionmentioning
confidence: 72%
“…Our findings are concordant with previous studies using SAFIRE-based CT. Kalra et al 18 compared the use of abdominal CT reconstructed with SAFIRE with CT reconstructed with FBP and demonstrated a 50% reduced dose and, in some patients, a 75% reduced dose when using SAFIRE without a loss of diagnostic value. Similarly, Winklehner et al 19 showed the potential to reduce the radiation dose by Ͼ50% in body CTA studies by using SAFIRE without a deterioration in image quality. In a chest CT study, Pontana et al 16 demonstrated a 50% lower dose while image quality was preserved.…”
Section: Discussionmentioning
confidence: 94%
“…Sinogram-Affirmed Iterative Reconstruction (SAFIRE) is a raw data and image domain-based 15 noise-modeling technique with 5 user-selectable strength levels. Previous work established the feasibility of SAFIRE for the study of body regions [15][16][17][18][19][20] and more recently in head CT 21 applications.…”
mentioning
confidence: 99%